University students' memories of their secondary science education experiences - Aydin, Semih; Kosarenko, Nikolay N.; Khlusyanov, Oleg V.; Malakhovskaya, Vera V.; Kameneva, Galina N. (Frontiers in Education, 2022)
Students' attitudes and ideas regarding a course, as well as their choice of career, are influenced by their previous educational experiences. This is also true for physics lessons, which are not exempt from this procedure. The attitudes of university students toward physics education during their high school years, as well as the teaching approaches employed in the course, as well as their opinions on studying physics, will all be investigated in this study. The research enrolled students majoring in education, engineering, and health sciences at a university in northern Iraq. The poll gathered data from 243 students. Researchers designed a survey that is used to collect data. Descriptive statistics, cluster analysis, the Mann-Whitney and Kruskal-Wallis tests were employed to address research questions. According to results, students' opinions about learning physics at the high school level can be accepted as positive. Attitudes and thoughts of students do not change according to gender, school status, grade level, or departments. The use of technology and the use of supportive course materials were effective in all dimensions